Effects of mammalian target of rapamycin inhibitors on cytokine production and differentiation in keratinocytes - DeTemple, Viola; Satzger, Imke; Walter, Antje; Schaper, Katrin; Gutzmer, Ralf (Experimental dermatology, 2016)
Risk factors for the development of cutaneous squamous cell carcinoma (cSCC) include ultraviolet radiation and immunosuppression. In particular, solid organ transplant recipients show a high incidence of cSCC, depending on the immunosuppressive regimen. While azathioprine or calcineurin inhibitors increase the risk of cSCC development, mammalian target of rapamycin (mTOR) inhibitors decreases this risk. At the moment, the mechanisms behind this protective effect of mTOR inhibitors are not fully understood. We evaluated effects of the mTOR inhibitors sirolimus and everolimus on keratinocytes, cSCC cell lines and an organotypic skin model in vitro in regard to proliferation, cytokine secretion and differentiation. We show that mTOR inhibitors block keratinocyte proliferation and alter cytokine and cytokeratin production: in particular, mTOR inhibition leads to upregulation of interleukin‐6 and downregulation of cytokeratin 10. Therefore, mTOR inhibitors have effects on keratinocytes, which could play a role in the pathogenesis of cSCC.